2020
DOI: 10.21580/jnsmr.2020.6.2.11225
|View full text |Cite
|
Sign up to set email alerts
|

Parasicity level of Telenomus sp. parasitoid against Spodoptera frugiperda J. E. Smith eggs in the laboratory

Abstract: Telenomus sp. as a biological agent, can be used to control a new pest, namely Spodoptera frugiperda which attacks maize in Indonesia. The purpose of this study was to count the number of eggs of S. frugiperda parasitized by Telenomus sp. and to calculate the level of parasitization of the parasitoid Telenomus sp. against S. frugiperda in the laboratory. Research method that used in this research were searching for S. frugiperda caterpillars and preparation of Telenomus sp. The data analysis used in this resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The different rates of parasitism are possible due to parasitoid conditions and different numbers of hosts. Putra & Wati (2020) reported that as the number of parasitoids that parasitized S. frugiperda eggs grew, the rate of T. remus parasitism also increased. Additionally, it was noted that when the number of provided hosts increased, the parasitism rate of Diaphania indica larvae by Apanteles taragamae did as well [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different rates of parasitism are possible due to parasitoid conditions and different numbers of hosts. Putra & Wati (2020) reported that as the number of parasitoids that parasitized S. frugiperda eggs grew, the rate of T. remus parasitism also increased. Additionally, it was noted that when the number of provided hosts increased, the parasitism rate of Diaphania indica larvae by Apanteles taragamae did as well [29].…”
Section: Discussionmentioning
confidence: 99%
“…As a critical step in preparing potential biological agents, parasitoids' ability must be tested on a laboratory scale. Meanwhile, research on the ability of natural enemies, such as the parasitoid S. frugiperda, on a laboratory scale in Indonesia is still limited to the egg parasitoid T. remus (18,19). In the current study, research was done to compare the performance of several parasitoids in controlling S. frugiperda.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were primarily focused on the presence/absence, diversity, infestation level, and ecology of S. frugiperda [5,[29][30][31][32]. Research on the performance of local parasitoid species in Indonesia in parasitizing S. frugiperda on a lab scale has even been reported [33,34]. Surveys on the infestation level of S. frugiperda, the association between S. frugiperda with local parasitoids, and its associated parasitism rate have also been carried out but are limited to a specific period [2,5,[35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…These studies were mostly focused on the presence/absence, diversity, infestation level, and ecology of S. frugiperda [5,[28][29][30][31]. Research on the performance of local parasitoid species in Indonesia in parasitizing S. frugiperda on a lab scale has even been reported [32,33]. Surveys on the infestation level of S. frugiperda, the association between S. frugiperda with local parasitoids, and its associated parasitism rate have also been carried out but are limited to a specific period [2,5,[34][35][36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%